Verbal distributional model as a theoretical and methodological tool of historical syntax - Vazhnik, Syarhei A. (Journal of the Belarusian State University. Philology, 2025)
The publication substantiates the expediency of using the contrastive approach when conducting research in the field of historical syntax: when comparing two sections of the Belarusian literary language – syntactic models of a simple sentence of the early 20th century and the structures of the early 21st century that are related to them. Comparison of syntactic facts of the Belarusian language in a hundred-year perspective is carried out by means of contrastive distributional analysis in order to identify differences in archaic syntactic models, identify syntactic specifics in the archaic version of a simple sentence of the Belarusian literary language of the early 20th century compared to the modern version. As a tool suitable for describing the above-identified fragment of syntactic systems, we propose to consider the verbal distributional model, which in this paper plays the role of the third component of comparison. The theoretical and methodological foundations of the verbal distributional model are described. The structure of the verbal distributional model is described in detail, which includes logical-semantic (propositional), categorical-semantic (selective), formal-grammatical and lexical levels. A contrastive typology of syntactic models is constructed, in which we distinguish identical, equivalent and nonequivalent structures.